MAKNA TEMBANG JAWA DALAM TRADISI MITONI DI DESA NGASEM KECAMATAN DANDER KABUPATEN BOJONEGORO JAWA TIMUR - Dewi, Tiara Puspita (TANDA, 2022)
The mitoni tradition is one of the Javanese customs which is carried out to commemorate the first pregnancy when the pregnancy reaches seven months. This tradition is full of cultural and spiritual values, one of which is reflected through the use of Javanese songs. This research aims to analyze the meaning of Javanese songs used in the mitoni tradition in Ngasem Village, Dander District, Bojonegoro Regency, East Java. Using the literature study method, this research examines various secondary sources, such as books, journal articles, and local documents that discuss Javanese mitoni and tembang traditions. The results of the analysis show that Javanese songs in the mitoni tradition not only function as entertainment, but also have deep symbolic meaning. These songs describe the hope for the safety of mothers and babies, balance in life, and strengthening the spiritual relationship with God. This research emphasizes the importance of maintaining and preserving the mitoni tradition, including Javanese songs which contain local values ​​and cultural wisdom.